Effects of edamame (glycine max) extracton post-prandial serum triglyceride in wistar rats - Kamal, Imran H; Dewanti, Linda; Wironegoro, Rio (Folia Medica Indonesiana, 2017)
Edamame (Glycine max) is a preparation of immature soybeans in the pod, which is high in calcium and dietary fiber, two elements described in previous studies that could alter the level of post-prandial serum triglyceride.The purpose of this research is to analyze the effect of edamame (Glycine max) extract on post-prandial serum triglyceride in rats after intragastric administration of palm oil.The materials used in this study are palm oil, edamame extract, and ether. The design of this study is experimental post-test study design, which is a design to measure the serum triglyceride level after meal with and without Glycine max. Triglyceride is measured on each subject two times on total, first one after consumption of meal without Glycine max and the second one after consumption of meal with Glycine max. There is a washout period of 1 week between two times the samples were taken. Both results are then compared in every subject.The level of 2-hour post-prandial serum triglyceride in rats after palm oil without intragastric edamame (Glycine max) extract administration and with intragastric edamame (Glycine max) extract administration showed no significant difference. In conclusion, edamame (Glycine max) extract had no effect on 2-hour post-prandial serum triglyceride after palm oil administration via intragastric tube.